2015
DOI: 10.1016/j.bpj.2014.09.049
|View full text |Cite|
|
Sign up to set email alerts
|

Stochastic Interdigitation as a Toughening Mechanism at the Interface between Tendon and Bone

Abstract: Reattachment and healing of tendon to bone poses a persistent clinical challenge and often results in poor outcomes, in part because the mechanisms that imbue the uninjured tendon-to-bone attachment with toughness are not known. One feature of typical tendon-to-bone surgical repairs is direct attachment of tendon to smooth bone. The native tendon-to-bone attachment, however, presents a rough mineralized interface that might serve an important role in stress transfer between tendon and bone. In this study, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 47 publications
1
62
0
Order By: Relevance
“…At the micrometer length scale, the interface between the mineralized and unmineralized tissues exhibits a waviness or interfacial roughness. In silico models have shown that a wavy interface between two dissimilar materials can serve to increase interfacial toughness at the cost of interfacial strength [42]. An increase in peak height (A) versus peak width (k), as measured by the A/k ratio, increases the magnitude of stress concentrations, leading to a decrease in strength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the micrometer length scale, the interface between the mineralized and unmineralized tissues exhibits a waviness or interfacial roughness. In silico models have shown that a wavy interface between two dissimilar materials can serve to increase interfacial toughness at the cost of interfacial strength [42]. An increase in peak height (A) versus peak width (k), as measured by the A/k ratio, increases the magnitude of stress concentrations, leading to a decrease in strength.…”
Section: Resultsmentioning
confidence: 99%
“…1). In silico studies examining interdigitating interfaces indicated that the waviness of an interface affects both its strength and toughness [5]. Uniformly increasing amplitude and frequency of the interfacial waviness results in a decrease in interfacial strength due to an increase in stress concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…[1,25,164] The native enthesis contains a dense network of collagen fibers interdigitated into bone that aid in tensile and compressive load transmission. [165168] The loading environment of the enthesis provides mechanical cues to cells that instruct matrix production and remodeling. Lack of loading during native development results in impaired mineral deposition and disorganized fiber distribution.…”
Section: Construct Maturationmentioning
confidence: 99%
“…Interactions between collagen and mineral are central to the mechanics and resilience of bone [20,21] and its interfaces with soft tissues [22,23]. A range of phenomenological and mechanistic models exist for the strength and toughness of bone, as reviewed by Jasiuk et al [24].…”
Section: Mineral -Collagen Interactionsmentioning
confidence: 99%